Creation of meanings in educational processes: Teaching practices with playful and experimental activities in the teaching of chemistry - Almeida , Amanda Klamer de; Welter , Cristiane Backes (Seven Editora, 2023)
This chapter aims to share partial results of a research that evaluated the development of a Potentially Significant Teaching Unit on the organic function of alcohol in Chemistry classes, with emphasis on recreational and experimental activities. The execution of the qualitative research, with the case study approach, took place in the months of February and March 2023, in a state school, in the municipality of Bom Jesus, with the participation of students from the third year of high school. The relevance of this study lies in the finding that, by using playful and experimental activities in teaching practices in different educational processes involving the Teaching of Chemistry, we create in students different senses with a view to meaningful learning. The discursive textual analysis allowed the construction of metatext that pointed to the construction of knowledge through the awakening of students’ interest by using playful and experimental activities created by teachers in Potentially Significant Teaching Units. DOI:https://doi.org/10.56238/ptoketheeducati-067